Sounds from Foreign Shores: Non-Traditional String Instruments and the Irish Folk Music Movement 1960–1979. Issue 1 (3rd July 2021) - Ó Luain, Breandán Seosaimh; Forbes, Anne-Marie
Abstract: The socio-political revolution of the 1960s and 1970s, and the simultaneous explosion in the commercialization of popular music, brought a period of rapid growth and change in Irish music, challenging divisions between folk and traditional music in both repertoire and instrumentation. This growth and change were driven by a diverse range of instrumental, structural and stylistic changes, coupled with a global investment in music and live performance as a commodity. Key ensembles such as The Dubliners, Sweeney's Men, Planxty, The Bothy Band and others explored new timbres while establishing a distinctively Irish, yet individual sound. This article explores the ways in which non-traditional string instruments were integrated into Irish ensembles, the technical and stylistic adaptations that resulted, and the legacy of this formative period in Irish music.